Selisih Dua Bilangan Bulat Yang Terbentuk Dari Angka-Angka Yang Sama Terbagi Sembilan (Jurnal Pilar Sains, 2006)
The integers which equivalent is the integer which formed by that same digit with the different arrange.Example, X and Y is any two integer which equivalent, so, the dispute from X and Y (X-Y or Y-X)divided of nine in symbolic way X-Y≡ 0 (modulo 9). Already done the searching of literature by doingeither inductive approaching or deductive to prove that X-Y congruent 0 modulo 9.